In-depth characterization of miRNome in papillary thyroid cancer with BRAF V600E mutation - Azliana Mohamad Yusof; Francis Yew Fu Tieng; Rohaizak Muhammad; Shahrun Niza Abdullah Suhaimi; Isa Mohamed Rose; Sazuita Saidin; Rahman Jamal; Imilia Ismail; Nurul-Syakima Ab Mutalib (Progress in Microbes and Molecular Biology)
MicroRNAs (miRNAs) are small non-coding RNAs, which play a critical regulatory role in papillary thyroid carcinoma (PTC). BRAF V600E is a hotspot mutation occurring in a majority of PTC cases and is proposed to be associated with poor clinical outcomes. The relationship between BRAF V600E status and miRNA expression in PTC has not been comprehensively studied. In this study, we aimed to identify the differentially expressed miRNAs in PTCs with and without BRAF V600E in an unbiased manner. Five fresh frozen thyroid cancer tissues paired with their respective adjacent normal tissues from PTC patients were subjected to BRAF V600E genotyping using Sanger sequencing and small RNA deep sequencing (miRNAseq). MiRNAs differentially expressed between BRAF V600E-positive and BRAF V600E-negative PTC tissues were validated in silico using The Cancer Genome Atlas (TCGA) THCA datasets containing 420 samples. MiRNA target prediction and pathway enrichment analysis were performed to identify biological pathways altered in this cancer. We identified 174 differentially expressed miRNAs; 80 were significantly over-expressed, while 94 were underexpressed (adj. p-value < 0.1; log2 fold change ≤ -1 or ≥ 1). Fifteen miRNAs were significantly differentially expressed only in BRAF V600E-positive PTC, and eight of these were validated in TCGA THCA dataset (hsa-miR-212, -132, -135b-3p/5p, -200b, -200a-3p/5p, -27a-3p/5p, -29a and -1296). Subsequent analysis revealed significant enrichment of cancer-related pathways including proteoglycans in cancer, ECM-receptor interaction and MAPK pathways in BRAF V600E-positive PTC. Using the miRNAseq and in silico validation using TCGA THCA study, we identified eight miRNAs that were differentially expressed in PTC tissues with BRAF V600E. This study also complemented the existing knowledge about deregulated miRNAs in PTC development.